Early mobilization in intensive care unit in Latin America: A survey based on clinical practice - Barros-Poblete, Marisol; Bernardes Neto, Saint-Clair; Benavides-Cordoba, Vicente; Vieira, Rodolfo P.; Baz, Manuel; Martí, Joan-Daniel; Spruit, Martijn A.; Torres-Castro, Rodrigo (Frontiers in Medicine, 2022)
Background: The application of early mobilisation (EM) in intensive care units (ICUs) has shown to improve the physical and ventilatory status of critically ill patients, even after ICU stay. This study aimed to describe the practices regarding EM in ICUs in Latin America. Methods: We conducted an observational, cross-sectional study of professionals from all countries in Latin America. Over three months, professionals working in ICU units in Latin America were invited to answer the survey, which was designed by an expert committee and incorporated preliminary questions based on studies about EM recommendations. Results: As many as 174 health professionals from 17 countries completed the survey. The interventions carried out within each ICU were active mobilisation (90.5%), passive mobilisation (85.0%), manual and instrumental techniques for drainage of mucus secretion (81.8%), and positioning techniques (81%). The professionals who most participated in the rehabilitation process in ICUs were physiotherapists (98.7%), intensive care physicians (61.6%), nurses (56.1%), and respiratory therapists (43.8%). In only 36.1% of the ICUs, protocols were established to determine when a patient should begin EM. In 38.1% of the cases, the onset of EM was established by individual evaluation, and in 25.0% of the cases it was the medical indication to start rehabilitation and EM. Conclusion: This report shows us that EM of critically ill patients is an established practice in our ICUs like in other developed countries.